2019
DOI: 10.3989/scimar.04883.11a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental variability on abundance of commercial marine species in the northern Gulf of California

Abstract: Studies have shown that environmental variables significantly affect variation in stock abundance of marine populations. The northern Gulf of California (NGC) is a highly productive region of interest due to its fish resources and diversity. Conservation of the marine species inhabiting the region is of public interest. Our study analysed the influence of physical environmental factors on several commercial marine species, using catch per unit effort (CPUE) as a proxy for abundance. Generalized additive models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In this current study, the condition index (K) was higher during winter than in the rest of the climatic seasons, where a recovery in the condition of octopus P. digueti was seen during autumn, decreasing in spring and increasing during the summer. In general, these variations could be caused by many factors such as reproductive activity, dietary changes and environmental factors (Ramirez and De la Cruz, 2015;Ruiz-Barreiro et al, 2019). The trend observed in the present study for the K index may be caused by the incidence of ovigerous females found in shelters.…”
Section: Fulton's Condition Index (K)supporting
confidence: 57%
“…In this current study, the condition index (K) was higher during winter than in the rest of the climatic seasons, where a recovery in the condition of octopus P. digueti was seen during autumn, decreasing in spring and increasing during the summer. In general, these variations could be caused by many factors such as reproductive activity, dietary changes and environmental factors (Ramirez and De la Cruz, 2015;Ruiz-Barreiro et al, 2019). The trend observed in the present study for the K index may be caused by the incidence of ovigerous females found in shelters.…”
Section: Fulton's Condition Index (K)supporting
confidence: 57%
“…Now, the discharge of the river was almost completely dependent on the freshwater influx from the Tigris River as a result of diverting the flow of Karun River inside the Iranian boundaries and cut off the Euphrates River before influx to the Basrah province (Mohamed and Abood, 2017). The impacts of freshwater inflow to estuarine systems as well as the influence of natural and anthropogenic factors have been discussed by several scientists (Gillson, 2011;Taylor et al, 2014;Ruiz-Barreiro et al, 2019;Osadchiev et al, 2020). Jesintha and Madhavi (2020) stated that the construction of dams diverts nutrient-rich water from entering into the sea, and obstruct the migratory path of some fish.…”
Section: Introductionmentioning
confidence: 99%
“…The abundance and distribution patterns of elasmobranchs can be affected by interannual changes in water temperature associated with climatic anomalies such as El Niño Southern Oscillation (ENSO) and its variations between warm (El Niño) and cold (La Niña) conditions (Arnés‐Urgellés et al, 2021; Osgood et al, 2021; Ruiz‐Barreiro et al, 2019). Further studies are necessary to analyse the impact of these climatic anomalies on the distribution of analysed round rays by maturity stages in the Gulf of California.…”
Section: Discussionmentioning
confidence: 99%
“…An annual reproductive cycle has been reported for Urobatis halleri in California (Babel, 1967;Mull et al, 2010), whereas a biannual reproductive cycle, with ovulation coinciding with parturition, has been described for the yellow stingray Urobatis jamaicensis (Cuvier, 1816) in south-east Florida (Schieber et al, 2023). and its variations between warm (El Niño) and cold (La Niña) conditions (Arnés-Urgellés et al, 2021;Osgood et al, 2021;Ruiz-Barreiro et al, 2019). Further studies are necessary to analyse the impact of these climatic anomalies on the distribution of analysed round rays by maturity stages in the Gulf of California.…”
Section: Discussionmentioning
confidence: 99%